Figurative Language in The Song Lyrics of Billie Eillish “Don’t Smile At Me” - Sharon Ladisa Julianto; I Nyoman Sedeng; Novita Mulyana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aimed to identify the types and meanings of figurative language applied in the song lyrics of Don’t Smile At Me album by Billie Eillish with the hope that readers can understand more about figurative language in depth. The documentation methods were combined with note-taking techniques to collect the data. To analyse the collected data this study applied descriptive and qualitative methods. Furthermore, the theory of Kennedy (1987)) was used to describe the figurative language expressed in the study. The analysis of this study shows that all types of figurative language are found in the song lyric. They are allusion, metaphor, hyperbole, irony, metonymy, , personification and simile. The most dominant figurative language found in the song lyric is metaphor.. To classify the types of meaning in the song lyric, the theory of Leech (1981) was used as the supporting theory. There are seven types of meaning proposed by the theory, thus this study found two of them namely, conceptual meaning, and connotative meaning. The figurative language used in the song lyric mostly expresses connotative meaning. Only a few of them express conceptual meaning.